2014
DOI: 10.1158/1538-7445.am2014-3363
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3363: Inhibition of glycolysis and proliferation of colon cancer cells by 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one (3PO) an inhibitor of 6-phosphofructo-2-kinase (PFKFB3)

Abstract: In human colon cancer cells, glycolytic activity shows a positive correlation with proliferation. PFKFB3 is an important enzyme regulating glycolysis in many tumor cells. We have studied the action of an established inhibitor of PFKFB3, 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one (3PO) as a single agent and in combination with other molecules that affect glycolysis and proliferation in four colon cancer cell lines (Caco-2, HCT116, HT29 and SW1116). Glucose uptake and cell proliferation were inhibited by 3PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The formation of NETs is strictly dependent on exogenous glucose and glycolysis 48 and the release of ETs has also been associated with glycolysis 29,33,50 . In the present study, we found that inhibiting glycolysis with 3PO reduces the uptake of 2‐deoxyglucose and the secretion of PFKFB3, a glycolytic enzyme activator 51,52 . STF‐31, a GLUT1 inhibitor, blocks glucose uptake and induces the apoptosis of GLUT1 myeloma cells 53 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The formation of NETs is strictly dependent on exogenous glucose and glycolysis 48 and the release of ETs has also been associated with glycolysis 29,33,50 . In the present study, we found that inhibiting glycolysis with 3PO reduces the uptake of 2‐deoxyglucose and the secretion of PFKFB3, a glycolytic enzyme activator 51,52 . STF‐31, a GLUT1 inhibitor, blocks glucose uptake and induces the apoptosis of GLUT1 myeloma cells 53 .…”
Section: Discussionsupporting
confidence: 55%
“…29,33,50 In the present study, we found that inhibiting glycolysis with 3PO reduces the uptake of 2-deoxyglucose and the secretion of PFKFB3, a glycolytic enzyme activator. 51,52 STF-31, a GLUT1 inhibitor, blocks glucose uptake and induces the apoptosis of GLUT1 myeloma cells. 53 Azd3965 inhibits the transport of lactic acid, promoting the accumulation of intermediate products during glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [74] recently demonstrated the use of HK2 as a single-cell sequencing-validated cellular marker for the high-throughput screening of highly glycolytic exfoliated UBC cells in urine, a method that showed sensitivity, specificity, positive predictive value, and negative predictive value superior to that of urinary cytology, accurately detecting BC before this standard method. A few preclinical reports have shown that the chemical inhibition of HK2 impaired the glycolytic activity of UBC cells by lowering glucose consumption and lactate production [75] and reduced the UBC cells' viability [76]. HK2 has been described as a crucial mediator of glycolytic activity in BC promoted by the long non-coding RNA UCA-1 [77,78]; additionally, the microRNA-21 inhibition in UBC cell lines resulted in decreased glycolytic activity, as seen by the reduced HK2 activity [72], which highlights the importance of epigenetic modifications in the UBC cells' metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This non-metabolizable glucose analogue has been widely used in preclinical assays, with promising results [85,86]. In BC specifically, proliferation was inhibited upon 2DG treatment in eight BC cell lines, and an additive effect was obtained with the coadministration of a PFK-related enzyme inhibitor [76]. 2DG markedly inhibited the UBC cells' viability, proliferation, lactate production, migration, invasion, and cell cycle progression and promoted cell death by apoptosis and necrosis in our "in vitro" experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this reagent has no inhibitory activity on the phosphorylation of fructose 6-phosphate and is nonspecific for PFK2 483 . The researchers designed and synthesized the PFKFB3 inhibitor 3PO based on the homologous model of PFKFB3 isozyme 484 , which has good anti-cancer activity in various types of tumor cells 485 , 486 , 487 . Due to the poor pharmacokinetic characteristics and low efficacy of 3PO 488 , subsequent researchers have improved its efficacy by loading nanocarriers into multiple types of cells 489 .…”
Section: Targeting Warburg Effect As Cancer Strategiesmentioning
confidence: 99%